Envisioning school autonomy to leverage culturally responsive learning: Evidence from East Java and East Nusa Tenggara - Sharfina Indrayadi; Riyandi Saras Anggita; Yulia Esti Utami (Center for Indonesian Policy Studies (CIPS), 2025)
Indonesia's socio-cultural and geographical diversity necessitates a decentralized education system, which has been in effect since the late 1990s. This decentralization enables schools to tailor education practices to local contexts, emphasizing culturally responsive learning (CRL) to accommodate diverse linguistic and cultural backgrounds. School autonomy, as reinforced by Law No. 20/2003 and Ministry of Education, Culture, Research and Technology Regulation No. 47/2023, grants schools authority and flexibility in terms of curriculum development, teacher management, and community engagement, which ensures education remains inclusive and contextually relevant. Policies such as the Merdeka Curriculum support CRL by granting regional policies the flexibility to facilitate local context learning across curricular and co-curricular activities. Local governments can operationalize this by developing targeted regulations concerning local content, teaching approaches, materials, and implementation strategies.
Keywords: 330